Analisis Fundamental Makro, Struktur Kepemilikan Terhadap Nilai Perusahaan dengan Karakteristik Perusahaan, Kinerja Keuangan dan Struktur Modal Sebagai Variabel Intervening pada Perusahaan Real Estate yang Terdaftar di BEI - Sihaloho , Yolanda Maghdalena; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to analyze the effect of macro fundamentals and ownership structure on firm value with company characteristics, financial performance, and capital structure as intervening variables in real estate companies listed on the Indonesia Stock Exchange for the period 2013-2023. Using quantitative methods, this study analyzed the financial statements of 3 companies selected through purposive sampling from a population of 84 real estate companies. The results showed that macro fundamentals have a significant effect on capital structure, but no significant effect on financial performance, company characteristics, and firm value. Ownership structure has a significant effect on capital structure, but has no significant effect on firm value, firm characteristics, and financial performance. Firm characteristics and capital structure have a significant effect on firm value, while financial performance has no significant effect. Of the 11 hypotheses proposed, only 3 are accepted. This finding indicates that in the real estate companies studied, firm characteristics and capital structure have a more significant influence on firm value than other factors. This study provides new insights into the factors that influence firm value in the real estate industry in Indonesia and can be a consideration for stakeholders in making decisions related to investment and management of companies in this sector.